Evaluation of Mild Childhood Asthma with Bronchial Hyperreactivity, the Number of Eosinophil and Serum Eosinophil Cationic Protein as a Marker of Disease Activity - Suehiro, Yutaka; Owa, Kenji; Kamesaki, Saori; Shinomiya, Keisuke (Japanese Journal of Pediatric Pulmonology, 1996)
To evaluate 13 mild childhood asthmatics (aged [mean±SD] 11.3±3.5 yr), bronchial hyperreactivity, the number of eosinophil and serum eosinophil cationic protein were measured. All were considered mild in severity based on the symptoms according to the classification of the Japanese Society of Pediatric Allergy and Clinical Immunology . The average number of peripheral eosinophil was 677±394/mm3 (ranged from 195 to 1616). The ECP mean concentration was 32.46±15.18μg/l (ranged from 4.35 to 54.35). The ECP levels of 12 out of 13 subjects proved to be above normal. The geometrical mean of PC20 methacholine was 490.9μg/ml ranged from 92.7 to 16117.1μg/ml. The ECP levels and PC20 methacholine covered a wide range although all of these childhood asthmatics were considered mild clinically. These observations suggest that the childhood anthmatics considered mild according to symptoms may still have bronchial hyperreactivity possibly due to persistent allergic inflammation.